2005
DOI: 10.1192/bjp.186.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Repeated self-poisoning: increasing severity of self-harm as a predictor of subsequent suicide

Abstract: BackgroundPrediction of suicide risk is difficult in clinical practice.AimsTo identify changes in clinical presentation predictive of suicide in patients treated for repeated episodes of self-poisoning.MethodA nested case–control study used the Hunter Area Toxicology Service database to identify exposure variables and the National Death Index to identify suicide. Cases were patients who had hospital treatment on more than one occasion between 15 January 1987 and 31 December 2000.ResultsThere were 31 cases, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 24 publications
3
49
1
1
Order By: Relevance
“…Likewise, the risk of an increased intensity of the medical treatment required (intensive care compared to ER/medical admission) among frequent attempters would be explained if repetition escalates the severity of subsequent SAs (Haw et al, 2007).Repeated deliberate self-harm (Zahl and Hawton, 2004) or SA (Christiansen and Jensen, 2007;Nordentoft, 2007) has been frequently associated with a higher risk of suicide death. Epidemiological data also supports that the severity of the SA increases with repeat attempts, possibly explaining the increased risk for subsequent completed suicide (Carter et al, 2005;Malone et al, 1995).…”
Section: Pathway Of Frequent Suicide Attemptsmentioning
confidence: 70%
See 1 more Smart Citation
“…Likewise, the risk of an increased intensity of the medical treatment required (intensive care compared to ER/medical admission) among frequent attempters would be explained if repetition escalates the severity of subsequent SAs (Haw et al, 2007).Repeated deliberate self-harm (Zahl and Hawton, 2004) or SA (Christiansen and Jensen, 2007;Nordentoft, 2007) has been frequently associated with a higher risk of suicide death. Epidemiological data also supports that the severity of the SA increases with repeat attempts, possibly explaining the increased risk for subsequent completed suicide (Carter et al, 2005;Malone et al, 1995).…”
Section: Pathway Of Frequent Suicide Attemptsmentioning
confidence: 70%
“…Accurate identification of high-risk suicide attempters is crucial to the development and implementation of targeted interventions to be provided according to the potential for reattempt and the available resources (Carter et al, 2005). In this study, we used a variable selection technique, Causal Discovery (CD), which is useful for both interpretation and prediction of relationships between variables (Pearl, 2000;Spirtes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…If one follows a sample with multiple, medically severe attempts, the rate of completion is higher. For example, in a study of 31 cases of completion after repeated self-poisoning, Carter and colleagues 28 reported that multiple attempts with increasing severity were associated with a significantly higher rate of suicide.…”
Section: Suicide Attempts and Suicide Completionmentioning
confidence: 97%
“…Outros estudos demonstram que a associação entre a história de tentativa de suicídio anterior e transtornos mentais aumentam em 5 a 6 vezes o risco para novas tentativas e suicídio, principalmente nos casos com maior letalidade 48,54,55,56,57 .…”
Section: A Prevalência Dos Transtornos Mentaisunclassified